2004
DOI: 10.1139/z04-003
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of northern redbelly dace, Phoxinus eos, to chemical alarm cues

Abstract: The northern redbelly dace, Phoxinus eos (Cope, 1862), is subject to predation by brook trout, Salvelinus fontinalis (Mitchill, 1814), in Canadian Shield lakes, particularly when individuals migrate to the pelagic zone at sunset to feed on zooplankton and fish shoals break up into single individuals. The objectives of the present study were to (i) determine whether northern redbelly dace react to skin extracts from conspecifics and thus potentially use chemical alarms to detect predators in nature, (ii) charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 55 publications
3
35
0
Order By: Relevance
“…The relative concentration of alarm cue detected should be directly related to proximity to a predation event, and as such, prey fishes should be able to assess local predation risk based on the concentration of alarm cue detected (Lawrence & Smith 1989, Dupuch et al 2004. Prey capable of adjusting the intensity of their antipredator response should be at a selective advantage, as they would be able to optimize the threat-sensitive trade-off between predator avoidance and foraging benefits (Helfman 1989).…”
Section: Discussionmentioning
confidence: 99%
“…The relative concentration of alarm cue detected should be directly related to proximity to a predation event, and as such, prey fishes should be able to assess local predation risk based on the concentration of alarm cue detected (Lawrence & Smith 1989, Dupuch et al 2004. Prey capable of adjusting the intensity of their antipredator response should be at a selective advantage, as they would be able to optimize the threat-sensitive trade-off between predator avoidance and foraging benefits (Helfman 1989).…”
Section: Discussionmentioning
confidence: 99%
“…When released, following mechanical damage to the skin, these cues can elicit dramatic short-term increases in species typical antipredator behaviours (Chivers & Smith 1998;Wisenden & Chivers 2006). Recent studies suggest that there is often a strong relationship between the relative concentration of alarm cues prey detect and the intensity of the antipredator responses displayed by the prey (Jachner & Rydz 2002;Dupuch et al 2004;Brown et al 2006aBrown et al , 2009). Moreover, prey may attend to alarm cues at very low concentrations by increasing vigilance towards secondary risk assessment cues (Brown et al 2004) or may show subtle adjustments in their foraging tactics (Foam et al 2005a).…”
Section: Chemosensory Cues As Sources Of Informationmentioning
confidence: 99%
“…They often elicit a dramatic increase in antipredator behaviour when detected by conspecifics and some heterospecifics (reviewed by Chivers & Smith 1998). Experimental manipulations of alarm cue concentrations have shown that increased alarm cue concentrations elicit increases in the intensity of antipredator behaviour displayed by some fish (Dupuch et al 2004, Zhao & Chivers 2006, including fathead minnows (Ferrari et al 2005. While these chemicals likely did not primarily evolve as true alarm signals (Wisenden & Chivers 2005, Chivers et al unpublished data), prey responding to these chemicals have a selective advantage.…”
Section: Introductionmentioning
confidence: 99%